2022
DOI: 10.3389/fonc.2022.879563
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Prediction Model for Breast Cancer Prognosis Based on Depression-Related Genes

Abstract: BackgroundDepression plays a significant role in mediating breast cancer recurrence and metastasis. However, a precise risk model is lacking to evaluate the potential impact of depression on breast cancer prognosis. In this study, we established a depression-related gene (DRG) signature that can predict overall survival (OS) and elucidate its correlation with pathological parameters and sensitivity to therapy in breast cancer.MethodsThe model training and validation assays were based on the analyses of 1,096 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, few predictive models based on depression-associated genes (DRG) have been established. Wang ( 41 ) et al. established a signature consisting of 10-DRG that predicted OS, which performed well in predicting OS, especially for patients with TNBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few predictive models based on depression-associated genes (DRG) have been established. Wang ( 41 ) et al. established a signature consisting of 10-DRG that predicted OS, which performed well in predicting OS, especially for patients with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…However, few predictive models based on depression-associated genes (DRG) have been established. Wang (41) et al established a signature consisting of 10-DRG that predicted OS, which performed well in predicting OS, especially for patients with TNBC. However, this model involved many DRGs, making it difficult to determine a precise biomarker that predicts depression in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As a disease that is strongly associated with genetic abnormalities, the genome of BC is valuable for exploration. A large body of literature has reported good bioinformatics tools for BC, such as depression-related models, angiogenesis-related models, or lactate metabolism-related models [ 45 – 47 ]. However, no mitophagy-related signature of BC has been studied, which in our study showed excellent prognostic ability and was related to distinct immune cell infiltration patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an extensive review of the pertinent literature from the past ve years was conducted. Subsequently, 18 signature genes associated with diverse biological processes, including exosome (13,14), TP53 mutation (15), necroptosis(16), depression (17), pyroptosis(18), autophagy (7,19), immune (20)(21)(22), angiogenesis (23), cuproptosis(18, 20), tumor microenvironment (TME) (24), methylation (25), natural killer cell (26), lipid metabolism (27), were incorporated for comparative analysis. The mlMSG prognostic model exhibited superior C-index performance compared to nearly all models present in TCGA and GEO datasets (Fig.…”
Section: Construction Of Prognostic Models Of Mlmsgsmentioning
confidence: 99%